Pandering judges - Stevens, M; Vidal, J (University of Oxford, 2008)
Tenured public officials such as judges are often thought to be indifferent to the concerns of the elctorate and, as a result, potentially lacking in discipline but unlikely to pander to public opinion. We investigate this proposition empirically using data on promotion decisions taken by senior English judges between 1985 and 2005. Throughout this period the popular view was one of ill-disciplined elitism: senior judges were alleged to be favouring candidates from elite backgrounds over their equally capable non-elite counterparts. We find no evidence of such ill-discipline; most of the unconditional difference in promotion prospects between the two groups can simply be explained by differences in promotion-relevant characteristics. However, exploiting an unexpected proposal to remove control over promotions from the judiciary, we do find evidence of pandering. When faced by the prospect of losing autonomy, senior judges began to favour non-elite candidates, as well as candidates who were unconnected to members of the promotion committee. Our finding that tenured public officials can display both the upsides and downsides of electoral accountability has implications for the literature on political agency, as well as recent constitutional reforms.